High frequency H-bridge inverter circuit for induction heaing rice cooker - Ishak @ A. Manap, Zulkarnain (1994)
This thesis describes the development of high frequency controller unit with H-bridge inverter circuit for induction heating rice cooker. The performance of this 3 8.4kHz controller and the dc to ac power MOSFET inverter in generating high frequency flux to heat steel, stainless steel and aluminium vessel has been investigated.